Interleukin‐13 and its signaling pathway is associated with obesity‐related colorectal tumorigenesis. Issue 7 (18th June 2019) - Matsui, Shimpei; Okabayashi, Koji; Tsuruta, Masashi; Shigeta, Kohei; Seishima, Ryo; Ishida, Takashi; Kondo, Takayuki; Suzuki, Yoshiyuki; Hasegawa, Hirotoshi; Shimoda, Masayuki; Sugimoto, Shinya; Sato, Toshiro; et al.
Abstract: The incidence of colorectal cancer (CRC) has been on the rise, which is linked to the increasing prevalence of obesity, based on global epidemiological evidence. Although chronic inflammation is implicated in tumor development, the mechanisms underlying obesity‐associated CRC remain unknown. Here, we sought to identify the inflammatory cytokines and their roles in obesity‐related colorectal tumorigenesis using cytokine array analyses in a mouse model. Colorectal tumorigenesis was induced through i.p. injection of azoxymethane once a week for 6 weeks in 6‐week‐old female WT C57Black/6J mice and the obesity diabetes model mouse KK/TaJcl, KK‐Ay/TaJcl. The formation of aberrant crypt foci and colorectal tumors were more frequent in obese mice compared with WT mice, and both serum interleukin (IL)‐13 and IL‐13 receptor (R) expression in the normal intestinal mucosal epithelium were significantly increased in the obese mice. Furthermore, addition of IL‐13 to a human CRC cell line and a human colon organoid culture altered the phenotype of intestinal epithelial cells. Knockdown experiments further revealed that IL‐13Rα1 dominantly induced mucosal proliferation. Collectively, These results suggest an association between anti‐inflammatory cytokines and colorectal carcinogenesis, and provide new research directions for cancer prevention strategies. In particular, inflammation provoked by obesity, notably by increased expression of the cytokine IL‐13, could play an important role in the carcinogenesis of obesity‐related CRC. Abstract : Interleukin (IL)‐13 and IL‐13 receptor expression in normal intestinal mucosal epithelium were significantly increased in obese mice. Inflammation provoked by obesity, notably an increased expression of the cytokine IL‐13, could play an important role in the carcinogenesis of obesity‐related colorectal cancer.